Rate of Decline in Nontreponemal Antibody Titers and Seroreversion After Treatment of Early Syphilis. Issue 1 (January 2017) - Seña, Arlene C.; Wolff, Mark; Behets, Frieda; Martin, David H.; Leone, Peter; Langley, Carol; McNeil, Linda; Hook, Edward W.
Abstract : Background: Syphilis management is complex and demonstration of treatment response requires monitoring of nontreponemal antibody titers for a ≥ 4-fold decline and/or seroreversion to nonreactive titers. Methods: We evaluated data from a multicenter clinical trial of syphilis treatment conducted from 2000 to 2009 involving human immunodeficiency virus (HIV)–negative patients 18 years or older with early syphilis. To assess the rate of titer decline and seroreversion after effective therapy, rapid plasma reagin (RPR) titers were analyzed at 1, 3, 6, 9, and 12 months among patients with an appropriate treatment response. We plotted the rate of RPR titer decline after treatment, estimated the frequency of seroreversion, and conducted multivariate analyses to assess characteristics associated with seroreversion. Results: Among 369 (79.4%) of 465 HIV-negative patients with early syphilis who had an appropriate treatment response, 333 participants had complete RPR data over 12 months. Although the decline in RPR titers was ≥ 4-fold among 88.0% (293/333) of participants at 3 months and ≥ 8-fold among 77.8% at 6 months, only 9.6% achieved complete RPR seroreversion at 6 months and 17.1% at 12 months after therapy. Male sex (adjusted odds ratio, 4.3; 95% confidence interval, 1.8–10.5) and baseline RPR titers ⩽ 1:32 (adjusted odds ratio, 14.5; 95% confidence interval, 6.8–31.2) were associated with higher odds of seroreversion compared with females and titers > 1:32, respectively. Conclusions: Despite a ≥ 4-fold RPR titer decline after treatment, the majority of HIV-negative patients with early syphilis failed to have seroreversion at 12 months. Nontreponemal antibody titers often persist despite an appropriate treatment response. Abstract : A study of human immunodeficiency virus–negative patients treated for early syphilis found that only 17% achieved complete seroreversion at 12 months despite an appropriate initial serological response after therapy.